Perubahan pH Saliva pada Anak Balita Stunting setelah Pemberian Kerupuk Singkong di Wilayah Kerja UPT Puskesmas Pekkae Kabupaten Barru - Nurul Annisa (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
The acidity level of saliva pH is one of the factors that influences oral health. In the context of toddlers experiencing stunting, high saliva pH acidity can increase the risk of serious oral health issues. This research aims to explore the potential impact of cassava chips consumption on changes in saliva pH in stunted toddlers. The study utilized an experimental pretest-posttest design. The research population consisted of 190 stunted toddlers in the working area of UPT Puskesmas Pekkae, Barru Regency, in May-July 2023. The sample comprised 16 stunted toddlers selected using purposive sampling. Data analysis was conducted using the Wilcoxon statistical test. The research results indicated that the consumption of cassava chips by stunted toddlers during the first four weeks resulted in a significant increase in saliva pH. There was a significant difference between saliva pH levels before and after consumption in the first week (p = 0.002), second week (p = 0.001), third week (p = 0.001), and fourth week (p = 0.001). However, in the fifth week, there was no significant change in saliva pH (p = 0.020). This means that cassava chips can increase saliva pH to a more neutral level in stunted toddlers during the first four weeks, but this change does not continue into the fifth week.